2017
DOI: 10.1371/journal.pone.0186385
|View full text |Cite
|
Sign up to set email alerts
|

One-time versus repeated abutment connection for platform-switched implant: A systematic review and meta-analysis

Abstract: ObjectiveThis review aims to compare peri-implant tissue changes in terms of clinical and radiographic aspects of implant restoration protocol using one-time abutment to repeated abutment connection in platform switched implant.MethodA structured search strategy was applied to three electronic databases, namely, Pubmed, Embase and Web of Science. Eight eligible studies, including seven randomised controlled studies and one controlled clinical study, were identified in accordance with inclusion/exclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 47 publications
1
38
1
1
Order By: Relevance
“…Connecting a final abutment without ever using a temporary one has its merits, not least by entailing fewer surgical visits and less tissue trauma. Studies have repeatedly demonstrated more favorable tissue outcomes in this way than after multiple abutment changes (Esposito et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Connecting a final abutment without ever using a temporary one has its merits, not least by entailing fewer surgical visits and less tissue trauma. Studies have repeatedly demonstrated more favorable tissue outcomes in this way than after multiple abutment changes (Esposito et al, ; Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review suggested that the OAOT protocol might preserve peri-implant bone loss and soft tissue changes for two reasons [57]. First of all, the micro-gap between abutment and implant could cause to bacterial leakage and micromotion, and this might lead to the inflammation of peri-implant soft tissue and bone resorption.…”
Section: Detachment Of Abutmentsmentioning
confidence: 99%
“…First of all, the micro-gap between abutment and implant could cause to bacterial leakage and micromotion, and this might lead to the inflammation of peri-implant soft tissue and bone resorption. The OAOT protocol could provide less micro-gap because healing or temporary abutments were installed by less preloading force (<10 Ncm) than final abutments (about 30 Ncm) [57]. Second, the OAOT protocol could reduce the disruption of the soft tissue seal around the implant abutment complex to avoid repeated the dis/reconnection of abutments [57].…”
Section: Detachment Of Abutmentsmentioning
confidence: 99%
“…79 Evaluated sites presented a higher number of titanium particles compared to healthy implants. [84][85][86] Although this limited crestal bone resorption does not seem to be clinically relevant, this established fact should at least raise the doubt that regular periimplant tissue probing assessments might repeatedly disrupt the soft tissue barrier with consequent serious iatrogenic effects on the stability of the peri-implant tissues in the long term. 81 There is strong evidence in the literature that the mechanical disruption of the mucosal barrier around an implant should be considered as a connective tissue wound resulting in epithelial proliferation to cover the wound, and in bone resorption to allow a connective tissue barrier of proper dimension to reform to re-establish a "biological width."…”
Section: On Factors With Particular Relevance For Oral and Orthopedmentioning
confidence: 99%
“…Repeated abutment dis/reconnections, with consequent disruption of the peri-implant soft tissue barrier, have been shown to cause crestal bone resorption around dental implants in animal studies 82,83 and in short-term and long-term clinical investigations as confirmed in several meta-analysis reports. [84][85][86] Although this limited crestal bone resorption does not seem to be clinically relevant, this established fact should at least raise the doubt that regular periimplant tissue probing assessments might repeatedly disrupt the soft tissue barrier with consequent serious iatrogenic effects on the stability of the peri-implant tissues in the long term.…”
Section: On Factors With Particular Relevance For Oral and Orthopedmentioning
confidence: 99%